Recurrent Teacher Cost per Student by Key Learning Area: Upper Secondary Schools, Victoria, Australia - Shah, Chandra (Education economics, 1998)
This paper reports the development of a model to analize direct teaching cost per student at the class level in Years 11 and 12, the final 2 years of secondary schooling in Victoria, Australia. Cost per student was modelled as a function of class size, teacher time developed to that class and teacher earnings. Class sizes were found to vary by subject or learning area and the school's total student enrolment in Years 11 and 12. The proportion of a class-teacher's total work time that is devoted to activities related directly to teaching the class was found to vary with the class was found to vary with the class teachers' sex, their appointment fraction and whether or not they had higher duties. It also varied with the class size, the enrolment in Years 11 and 12, and the learning area. Earnings were found to vary with the sex of the teacher, whether or not they had higher duties and the learning area they taught in, and to a smaller extent with the enrolment in Years 11 and 12. The model provides predictions for class size and unit cost for each learning area for various levels of enrolment in Years 11 and 12. Predictions of cost per student for foreign-language classes were almost twice as much as that for English classes, and mathematics classes had the lowest cost per student.